2017
DOI: 10.13189/adm.2017.050201
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Vitamin C and E Dose on Type 2 Diabetes Patients

Abstract: Diabetes is a metabolic disorder that causes vascular complications. As vitamin C and E is known for its beneficial effects on blood sugar, serum lipids and glycated haemoglobin (HbA1c). In the present study, we assess the combined effect of vitamin C and E on blood sugar (FBS), serum creatinine (SC), total cholesterol (TC), low and high density lipoprotein (LDL, HDL), and glycated haemoglobin (HbAIc) in type 2 diabetes mellitus patients. A total of 50 patients with type 2 diabetes referred to Rama Hospital (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…The results showed no significant difference between vitamin C intake and HbA1c. This supports the study conducted by Dakhale et al (2011); Hamed et al, (2016) and Prajapat et al (2017). Donin et al (2015) revealed the risk of type 2 diabetes was more determined by systemic vitamin C levels, rather than vitamin C intake.…”
Section: The Relationship Between Vitamin C Intake and Hba1csupporting
confidence: 85%
“…The results showed no significant difference between vitamin C intake and HbA1c. This supports the study conducted by Dakhale et al (2011); Hamed et al, (2016) and Prajapat et al (2017). Donin et al (2015) revealed the risk of type 2 diabetes was more determined by systemic vitamin C levels, rather than vitamin C intake.…”
Section: The Relationship Between Vitamin C Intake and Hba1csupporting
confidence: 85%
“…Diabetes mellitus is metabolic epidemic that occur due to ineffective secretion of insulin from pancreas [1,2] and the possibly the worldwide number of diabetic patient will be rise up to 439 million by 2030 [3,4]. Vitamin E supplementation could improve glycemic control in diabetes patients [5,6].Vitamin C supplementation is effective in prevention of non-enzymatic glycosylation of proteins [7] and it also serves as therapeutic agent for diseases that protects body from damage caused by free radicals [8].…”
Section: Introductionmentioning
confidence: 99%